A Program for Psychology in a College of Commerce and Administration - Richardson-Robinson, F.; Kingsbury, F. A.; Robinson, E. S. (Journal of Political Economy, 1922)
Psychology can contribute in two distinct ways to a course in commerce and business administration. Inasmuch as it represents the most systematic attempt to formulate the laws of human behavior, psychology is a fundamental science offering basic generalizations and working hypotheses to the intelligent consideration of problems of human action. Inasmuch as the psychologist has, in the development of his own science, produced technical methods formed in the light of the extreme variability of human activities, these methods can, in themselves, be offered to commerce and administration as a definite technology. The presentation of psychology as a fundamental science should have a constructive and a critical purpose. This constructive purpose can best be served by a systematic discussion of such topics as the following (the illustrative material to be drawn, where practicable, from business situations): (a) Working conception of the physical mechanisms of action. (b) Basic human incentives, tendencies, and attitudes, and the mechanism of their modification, development, or repression. (c) Factors in learning and economy of learning and retention, as in memory, habit, acts of skill. (d) Normal mental functions-attention, association, perception, remembering, thinking, volition, etc. (e) Personality and temperamental traits, their origins, types, measurement, and their organization into personality and character. (C) Conditions of efficiency in work; influence of interest, fatigue, age, sex, drugs, physical environment, rewards and incentives, etc. (g) Scope and distribution of individual and group differences, and methods of measuring them (standardized tests for special and general abilities, achievement tests of educational or trade type, judgments of associates, etc.). The critical purpose can be served by an examination of typical popular conceptions of mind and the pseudo-scientific conclusions